Modeling economic grhor.owth in contemporary India - Sergi, Bruno S.; Tiwari, Aviral Kumar; Nasreen, Samia (Entrepreneurship and global economic growth., 2024)
Despite rapid economic growth, the Indian economy is facing numerous social and developmental challenges which are a major hindrance to sustainability. This volume of the Entrepreneurship and Global Economic Growth series sheds light on economic and social challenges, policy reforms, and future dynamics and solutions. Modeling Economic Growth in Contemporary India focuses on core topics of economic disruption caused by the Covid-19 pandemic, changes in socio-cultural relationships, behavioural patterns and psychological attitudes governing human interaction, and government policies to stabilize the Indian economy and contribute to sustainable growth. Topics are explored such as macroeconomics, trade, manufacturing, agriculture and tourism to thoroughly examine the challenges to economic growth throughout India. Scholars, researchers, policy makers and management practitioners will benefit from understanding the effects of the pandemic in economic and social well-being terms to facilitate growth and fuel sustainable development strategies in India.